Pemberian berbagai komposisi bahan organik terhadap pertumbuhan dan hasil tanaman kacang panjang (Vigna Sinensis L.) dengan sistem pertanian berkelanjutan - Andi Setiawan; Suryani Sajar; Ihsan Proyogo (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
The purpose of this study was to understand the impact of optimizing organic matter and its composition on the development and productivity of long bean plants. The research was conducted from May to July 2023 at the location of Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency. The method used in this study was a non-factorial randomized group design (RAK) repeated 3 times. The treatments consisted of P0 = Inorganic fertilizer (17 gr/plot N, 15 gr/plot P2O5, 15gr/plot K2O) as control. P1= Cow dung compost 1.5 kg/plot; P2= Paitan 2 kg/plot; P3= Azolla compost 1.5 kg/plot; P4= Cow dung compost 0.75 kg/plot + Paitan 1 kg/plot; P5= Cow dung compost 0.75 kg/plot + azolla compost 0.75 kg/plot; P6= Cow dung compost 0.35 kg/plot + paitan 1.5 kg/plot; P7= Cow dung compost 0.35 kg/plot + azolla compost 1 kg/plot. The findings indicated that the application of organic substances in various scenarios showed similar impacts on all growth and yield parameters. The longest average plant length for all organic matter treatments at 4 weeks after planting was found in treatment P7 (Cow dung compost 0.35 kg/plot + Azolla compost 1 kg/plot) which was 70.40 cm while at 6 weeks after planting and 8 weeks after planting was found in treatment P2 (Paitan 2 kg/plot) which was 222.98 cm and 279.04 cm. The highest number of productive branches against all organic matter treatments at 6 weeks after planting was P4 (Cow dung compost 0.75 kg/plot + Paitan 1 kg/plot) which was 5.28 branches. The highest average number of fruits per sample at 7 weeks after planting is treatment P7 (Cow dung compost 0.35 kg/plot + Azolla compost 1 kg/plot) which is 68.40 fruits, while at 8 weeks after planting and 9 weeks after planting is P2 (Paitan 2 kg/plot) which is 222.98 cm 279.04 fruits.